Challenges in Roma Pupils’ Education and Their Overcoming: An Analysis of Lithuanian General Education School Teachers’ Experience - Survutaitė, Dalia (Pedagogika, 2023)
International organisations and the Council of Europe are articulating the challenges of Roma integration versus discrimination. It is acknowledged that the social exclusion of Roma people is related to social and educational problems and is regarded as a barrier to pupils’ successful education and development. The aim of the study is to reveal the challenges in the education of Roma pupils and their overcoming. One-fifth of Roma people in Lithuania (21.5%) are children and young people enrolled in general education. General education schools face challenges in educating Roma pupils. Therefore, it is important not only to know and understand such challenges but also to evaluate good practices for coping with them. Research studies have shown that Roma families experience social, economic, and cultural exclusion, which leads to problems in education of Roma pupils predetermined by such factors as social, economic, and cultural disadvantage and negative attitudes of the community and parents/guardians towards education. The latter obstacles lead to a lack of motivation to learn and consequent absenteeism. The factors identified as causes also result in consequences such as gaps in learning, academic failures, and, ultimately, dropping out of the education system. The challenges of educating Roma pupils can be addressed by implementing socially just education measures and employing the power of school culture.